Adolescent participation and the project cycle : three (Commonwealth Secretariat LondonGB, 2005)
Provides organising principles for discovering what roles adolescents and adults can play as part of the project development and implementation processes, and also for achieving adolescent participation at all stages of a project.
Keywords: DECISION MAKING